Two years amongst the Indians of Queen Charlotte's Island [electronic resource] - Poole, Francis ([S.l. : s.n., 1868)
Running title: Indians of Queen Charlotte's Island. Excerpt from Mission Life, Feb. 1, 1868. Caption title. Electronic reproduction. Mode of access: Internet. 44